Alien species richness is currently unbounded in all but the most urbanized bird communities. Issue 8 (4th April 2019) - Tsang, Toby P. N.; Dyer, Ellie E.; Bonebrake, Timothy C.
Abstract : Urban areas suffer high pressure of introductions of alien species compared to other habitats due to intensive human activities. As trading globally continues to rise, more species will likely be introduced into urban areas. To determine whether this increase in introduction pressure will lead to increased alien species richness in urban areas, or whether other processes would act to impose an upper limit on species richness, we examined how the shape of the relationship between alien species richness and the number of introduced species over time (i.e. introduction pressure) varies along gradients of urbanization. We collected species composition data from urban bird surveys worldwide and used a global database of alien bird introductions to quantify how many species have been introduced over time at different sites. We found that urbanization gradually modified the shape of the studied relationship from linear to asymptotic. Only communities in extremely urbanized environments were associated with an asymptotic relationship, suggesting that alien bird richness has likely not reached its ecological limit in most urban areas. Our results show that urbanization can reduce the importance of introduction pressure in determining alien species richness. Additionally, the results predict that alien species richness will increase at finer spatial scales, especially if the introduced species can survive in urban areas outside of their native range.